AUGMENTED RESEARCH ON DAILY-BASIS IMPROVEMENTS OF WELDING AND NDT ECONOMY IN SHIPYARDS - EL SEIDI, HUSSAM (Digital Repository of Theses - SSBM Geneva, 2022)
The welding process is expensive and represents a considerable part of the overall process of any shipyard. The shipbuilding welding target is to manufacture a sound hull with no welding defect and as stated by the rules, regulations, and international standards. The up-to-date information in the shipbuilding and from shipyards have shown the requirement for continuous research in the relevant welding sectors, nondestructive tests, and quality control and assurance during the shipbuilding phase. Adding new value based on hands-on experience gained in shipyards worldwide and problem areas that occur globally on a day-to-day basis and their smart measures has been considered thoroughly in this dissertation. Research has demonstrated the definite requirement in considering boosting the proficiency of production in shipyards and the cost-effectiveness. The fusing superiority and nondestructive tests are major factors. The optimum mutual joining procedures, most common materials and those most commonly applied in shipyards and shipbuilding, and quality control will be summarized—adding hands-on practical experience gathered in major shipyards—and this will lead to recommendations on how major factors could be better managed on how they could improve the quality, welding, and nondestructive tests economy alike, forming state-of-the-art research.